LAPTM5–CD40 Crosstalk in Glioblastoma Invasion and Temozolomide Resistance - Berberich, Anne; Bartels, Frederik; Tang, Zili; Knoll, Maximilian; Pusch, Sonja; Hucke, Nanina; Kessler, Tobias; Dong, Zhen; Wiestler, Benedikt; Winkler, Frank; Platten, Michael; Wick, Wolfgang; et al. (Frontiers in Oncology, 2020)
Background: Glioma therapy is challenged by the diffuse and invasive growth of glioma. Lysosomal protein transmembrane 5 (LAPTM5) was identified as an invasion inhibitor by an in vivo screen for invasion-associated genes. The aim of this study was to decipher the function of LAPTM5 in glioblastoma and its interaction with the CD40 receptor which is intensively evaluated as a target in the therapy of diverse cancers including glioma. Methods: Knockdown of LAPTM5 was performed in different glioma cell lines to analyze the impact on clonogenicity, invasiveness, sensitivity to temozolomide chemotherapy, and tumorigenicity in vitro and in vivo. An expression array was used to elucidate the underlying pathways. CD40 knockdown and overexpression were induced to investigate a potential crosstalk of LAPTM5 and CD40. LAPTM5 and CD40 were correlated with the clinical outcome of glioma patients. Results: Knockdown of LAPTM5 unleashed CD40-mediated NFκB activation, resulting in enhanced invasiveness, clonogenicity, and temozolomide resistance that was overcome by NFκB inhibition. LAPTM5 expression correlated with better overall survival in glioblastoma patients depending on CD40 expression status. Conclusion: We conclude that LAPTM5 conveyed tumor suppression and temozolomide sensitation in CD40-positive glioblastoma through the inhibition of CD40-mediated NFκB activation. Hence, LAPTM5 may provide a potential biomarker for sensitivity to temozolomide in CD40-positive glioblastoma.